Islamic Branding: Analisis Pengaruh Brand Identity Terhadap Brand Awareness Wardah Kosmetik - utami, neni; sujianto, agus eko (Universitas Muhammadiyah Surabaya, 2023)
Â This study aimed to examine the effect of Brand Identity on Brand Awareness among ASNs in Blitar Regency. The population used was 105 populations with 86 samples that fit the criteria, namely ASN and users of wardah cosmetics. Primary data is taken using a questionnaire distribution with a Likert scale of 1-5. The approach used is an associative quantitative approach. The tests carried out are validity tests, reliability tests, normality tests, simple regression tests, hypothesis tests, and coefficient of determination tests. The results of this study indicate that Brand Identity has a positive and significant effect on Brand Awareness of Wardah cosmetic products by 38.4%.Â Keywords: Cosmetic Industry, Islamic Branding, Brand Identity, Brand Awareness